Analysis of the Land and Building Tax Collection Process at the Regional Revenue Agency of North Tapanuli Regency - Bonifasius H. Tambunan; Yoga Xaferius Gurning; Bunga Avrilia Ebena Limbong; Risno Simaremare; Eunike Pasaribu (Indonesian Journal Economic Review (IJER), 2026)
Land and Building Tax (PBB) is one of the main sources of Local Revenue (PAD), playing a significant role in supporting regional fiscal independence. The effectiveness of PBB collection is crucial in determining the ability of local governments to finance development and public services. This study aims to analyze the PBB collection process conducted by the Regional Revenue Agency (BAPENDA) of North Tapanuli Regency, identify the challenges faced, and evaluate efforts to improve taxpayer compliance. The research method uses a qualitative descriptive approach with primary data obtained through direct observation during the Field Work Practice (PKL) activities, as well as secondary data in the form of agency documents and relevant literature. The results of the study show that PBB collection is carried out through administrative billing via the issuance and distribution of Tax Due Notice (SPPT) and field collection efforts targeting delinquent taxpayers. Major obstacles include low taxpayer awareness and understanding, geographical constraints, and limited resources. Improvement efforts include socialization activities, intensification of field collection, and the use of digital payment systems such as QRIS. This study is expected to contribute practically to improving the effectiveness of local tax management.